(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the role of magnetic resonance imaging in the preoperative staging of rectal cancer, particularly in assessing the depth of tumor invasion and regional lymph node metastasis, using postoperative histopathological findings as the reference standard. Subjects and methods: A retrospective cross-sectional study was conducted on 45 patients with rectal cancer who underwent preoperative magnetic resonance imaging and surgery at E Hospital between July 2022 and August 2025. Results: The mean age of the patients was 65.9 ± 11.2 years, with males accounting for 66.7%. Magnetic resonance imaging accurately determined the depth of rectal wall invasion in 91.1% of cases, with sensitivity ranging from 75-94.3% and specificity from 80-100% across tumor invasion stages. The accuracy for assessing lymph node metastasis was 75.6%, with sensitivity ranging from 66.7-87.5% and specificity from 82.8-91.7%. Conclusion: Magnetic resonance imaging is a highly valuable modality for the preoperative staging of rectal cancer. It allows precise evaluation of tumor extent and nodal involvement, thereby aiding in diagnosis, prognostication, and optimization of therapeutic strategies in clinical practice.